Speed of information diffusion within fund families - Gjergji Cici; Stefan Jaspersen; Alexander Kempf (University of Cologne, Centre for Financial Research (CFR), 2015)
We document that the speed of information dissemination within mutual fund families positively affects the performance of member funds. This suggests that the resulting benefits of higher information precision far outweigh free-riding costs associated with fast internal dissemination. The performance effect intensifies when information travels across managers from different rather than same styles. This is consistent with fast information diffusion aggregating complementary insights that sharpen information precision, but also with fewer free-riding opportunities among managers from different styles. Managers exploit the resulting higher information precision rationally by trading more, relying less on public information, and investing differently from unaffiliated peers.
Keywords: D23; D83; G23; L22; 330; Information diffusion; mutual fund performance; fund families; investment behavior; organizational structures